Penyuluhan Tentang Pentingnya Pendidikan Karakter Pada Era Digitalisasi Di SMP Ma’arif 10 Bangunrejo - Ozi Hendratama; Wayan Satria Jaya; Aurora Nadia Febrianti; Heni Saputri; Dhani Karyono (Yayasan Daarul Huda Kruengmane, 2026)
The purpose of this Community Service Program (PKM) is to provide counseling on the importance of character education in the digital era to students of SMP Ma'arif 10 Bangunrejo. This counseling uses interactive methods, focus group discussions, and case study simulations. The community service team strives to internalize the values of honesty, empathy, and digital responsibility. The target audience for this counseling is all students at SMP Ma'arif 10 Bangunrejo. The results of the activity show a significant increase in students' digital ethics literacy by 85% based on a post-activity evaluation. In addition, it was found that the approach that combines Ma'arif's distinctive religious values with modern digital skills can create critical awareness in students in responding to the phenomena of cyberbullying, hoaxes, and moral degradation on social media. The conclusion of this community service is that character building is an absolute foundation that students must have so that digitalization becomes a means of developing potential, not a trigger for moral decadence.